2013
DOI: 10.1088/0031-9120/48/6/736
|View full text |Cite
|
Sign up to set email alerts
|

Stacking up against alternative conceptions: using Uno cards to introduce discourse and argumentation

Abstract: We engaged secondary science students in a teacher and student constructed Uno card game (UCG) to change their conceptual understanding of the various energy transformations. The paper outlines how we incorporated Toulmin’s argumentation pattern (Toulmin  The Uses of Argument (Cambridge: Cambridge University Press)) in the UCG, using discourse (Erduran et al  Sci. Educ. 88 915–33) and through a 5E learning cycle (Bybee  Achieving Scientific Literacy: From Purposes to Practices (Portsmouth, NH: Heinemann Educa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Decades ago, A Nation at Risk identified a nationwide decline in science scores on national assessments and expressed serious concern about the state of science education and the potential for future generations of students to never fully develop scientific literacy (Gardner, Larsen, Baker, Campbell, & Crosby, ). This prompted increasing attention to the way science is taught and learned in classrooms, with student‐centered approaches, particularly inquiry‐based learning and recent attention to scientific practices (e.g., Demir & Ellett, ; Dunac & Demir, ; National Research Council [NRC], ; Zachos, Hick, Doane, & Sargent, ), attempting to increase both student engagement and achievement. However, recent reports have indicated that science classrooms are still not providing opportunities for students to engage in authentic scientific practices (National Science Board, ).…”
Section: Introductionmentioning
confidence: 99%
“…Decades ago, A Nation at Risk identified a nationwide decline in science scores on national assessments and expressed serious concern about the state of science education and the potential for future generations of students to never fully develop scientific literacy (Gardner, Larsen, Baker, Campbell, & Crosby, ). This prompted increasing attention to the way science is taught and learned in classrooms, with student‐centered approaches, particularly inquiry‐based learning and recent attention to scientific practices (e.g., Demir & Ellett, ; Dunac & Demir, ; National Research Council [NRC], ; Zachos, Hick, Doane, & Sargent, ), attempting to increase both student engagement and achievement. However, recent reports have indicated that science classrooms are still not providing opportunities for students to engage in authentic scientific practices (National Science Board, ).…”
Section: Introductionmentioning
confidence: 99%
“…The pattern of individual participation will increase. In some situations, the teacher encourages students to explain, using their language, the concept of energy transformation with the help of the TAP framework (Dunac & Demir, 2013). Argumentation skills by analyzing the results of essay tests on a controversial topic, namely pollution.…”
Section: Discussionmentioning
confidence: 99%
“…Ethnicity: 2011 (Provasnik et al, 2012, p. 58) Because research shows that most students of color reside in urban areas 2008), urban teachers of students of color have to balance the push for improvement in standardized test scores with what they believe is the true essence of learning science Demir, 2013;Li, Klahr, & Siler, 2006).…”
Section: Figure 2 Average Science Scores Of Usmentioning
confidence: 99%
“…Average science scores of U.S. 8 th grade students, by Race/ (Provasnik et al, 2012, p. 58) Because research shows that most students of color reside in urban areas hers of students of color have to balance the push for improvement in standardized test scores with what they believe is the true essence of learning science Demir, 2013;Li, Klahr, & Siler, 2006). It is important to note that when researchers dig into the literature they find that academic achievement data reflects the Eurocentric view of learning, where meaning is fixed and others with opposing views bring little to the science .…”
Section: Timssmentioning
confidence: 99%
See 1 more Smart Citation